Information seeking behavior of foreign students of the University of the Philippines Diliman - Reyes, Rico Marco B.; Lapuz, Elvira B. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2009)
Information seeking behavior has been the focus of inquiry within the Library and Information Science communities in the past decades. Earlier studies included user (demographics) and use studies for improving collection development. These were followed by studies that explored the research practices of individuals or groups to design appropriate systems and services to aid those habits. It was in the last decade when user studies evolved into the examination of information seeking behavior employing more holistic approaches (Tibbo, 2004). This study determined the information-seeking behaviors of foreign students of the University of the Philippines Diliman. This relates to how foreign students start to locate information materials, what methods they usually do to locate information needed and what information materials are found useful to them. The study also focused on finding out the relationships between certain factors that the information-seeking behavior of foreign students in terms of their success in finding the needed information in the library.
Ninety-three foreign students of the University of the Philippines Diliman were surveyed using questionnaires. Data were gathered and tabulated based on the answers of the respondents. Frequencies, averages and chi-square test of significance were used to analyze data.
The results obtained from the computations are: (1) foreign students (34.4) usually begin their search by using the Internet; (b) they (33) also begin their information search by asking a person, which could either be their classmate, professors, or librarians; (c) foreign students seldom search information from multimedia resources (weighted mean of 2.266), occasionally search reference sources (3.226), e-resources (3.344), and OPAC (2.892); (d) foreign students occasionally use both print and non-print materials (weighted mean of 4.118); (e) for most of the foreign students, it doesn't really matter where, when, and how long it will take them to search the information that they need; (f) it is important for most of the foreign students hat the information they will be getting should be reliable, accurate and relevant to their topic, and the information sources is easy for them to use; (g) 47.3 of the foreign students were successful in finding useful information in the library. Further analysis showed factors that affect the foreign students'students' overall perceived success in finding useful information in the library. Based on the computations, the findings of the study are: (a) Length of stay in the Philippines, over-all English language proficiency, and frequency of library use are significant to the foreign students'over-all perceived success of finding useful information in the library.
Recommendations include increasing the number of respondents to have more number of foreign students per nationality; comparison among local and foreign students' information-seeking behaviors could also be done to differentiate information needs; and different research methodology of determining information-seeking behaviors of foreign students.
Vita.
Thesis (Bachelor of Library and Information Science)
Keywords: Students, Foreign -- Philippines -- Quezon City; Library use studies -- Philippines -- Quezon City